Handwash Liquid Soap Formulation Contains Eucalyptus Globulus Extract - Kurniasari, Laviona Tiara; Wijayati, Nanik; Amalina, Nur Dina (Universitas Negeri Semarang, 2021)
Eucalyptus globulus is known as a medicinal plant because of its biological and pharmacological properties, making it suitable to be added to the manufacture of liquid hand soap. This study aims to formulate hand washing liquid soap containing Eucalyptus globulus extract and to determine the organoleptic test comparison of liquid hand washing soap Eucalyptus globulus compared to liquid hand washing soap without Eucalyptus globulus extract. In this study, hand soap was made with a formula of 0.5% Eucalyptus globulus essential oil. Several tests were carried out with organoleptic parameters and foam tests. The study showed that the formula made was clear in color, the odor parameter showed that the Eucalyptus globulus formula had a distinctive Eucalyptus odor while the formula without Eucalyptus globulus extract had a fruity aroma. The shape parameter shows that both formulations are liquid. In the foam test results, the formula for liquid handwashing Eucalyptus globulus compared to liquid handwashing soap without Eucalyptus globulus extract gave a foamy formulation. Organoleptic tests based on parameters of color, aroma, shape, ease of wiping on the palms, and evaporation speed to 5 untrained panelists showed that the panelists preferred Eucalyptus globulus liquid hand soap.